THE INHIBITING GRAMMATICAL RULES OF INDONESIAN IN THE ACQUISITON OF TENSES AND TO BE - Y. E. Budiyana (Soegijapranata Catholic University, 2002)
This article aims to examine briefly the implication of. Contrastive analysis hypothesisfor the Indonesian learners in learning English. By contrastive analysis is meant ;he analysis of the similarities and differences between LI (Indonesian) and 1.2 (English) in particular the inhibiting grammatical rules of Indonesian in the acquisition of tenses and to be. This value sIems from the fOCI that based on the observation. the Indonesian students tend to transfer the forms and meanings of their fintlanguage :Indonesian) into the target language (English) when they spealc and write in English. By knowing the difference and similarities between LI and 1.2. the trouble spots in TL could be anlicipated, errors might be prevented and at least held to be minimum, in this way the formation of bad habit could be avoided